EKSPLORASI PENGGUNAAN TEKNOLOGI AUGMENTED REALITY DALAM PENDIDIKAN AGAMA ISLAM UNTUK MEMPERKAYA PENGALAMAN PEMBELAJARAN DI SMP IT MUTIARA CENDEKIA LUBUKLINGGAU MUTIARA CENDEKIA - Sohah Andrian Sakban (UNISAN JURNAL, 2024)
The use of Augmented Reality (AR) technology in education is gaining attention due to its potential to enhance learning experiences. This study aims to explore the use of AR technology in the context of Islamic education in Integrated Islamic Junior High Schools (IT). The research method used is a qualitative approach with a case study design. Data were collected through participatory observation, interviews with teachers and students, and analysis of learning materials developed using AR technology. The results show that the use of AR technology has improved interaction between teachers and students, providing a more interactive and engaging learning experience for students. Students showed a high interest in learning with AR technology and stated that it made learning Islamic education more enjoyable and meaningful for them. However, the study also identified several challenges in the implementation of AR technology, including the availability of adequate technological infrastructure in schools and difficulties in developing AR content that aligns with the Islamic education curriculum. Therefore, there is a need for improvement measures such as investment in technological infrastructure, adequate teacher training, collaboration between education stakeholders, and government support to optimize the use of AR technology in Islamic education SMP IT Mutiara Cendekia Lubuklinggau. Overall, this study demonstrates that the use of AR technology has great potential to improve the quality of Islamic education and help students understand and internalize the teachings of Islam more deeply.